Application dispersed particle gels as in-situ fluid diversion agent - Naghiyeva, N. V. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2021)
From year to year, the number of fields in late stages of development is increasing, which is inevitably accompanied by a decrease in oil production rates and an increase in the volume of produced water. One of the most effective technologies for dealing with this problem is the application of flow diverting technologies. The paper presents the synthesis of the dispersed-gel particles (DPG) for modifying the injectivity profile of the well, the displacement front and diverting the filtration flows in the reservoir. A series of experiments were carried out to determine the particle size distribution, resistance factor of the proposed composition, both on sandpack models and on core samples was studied. The use of the DPG composition allows the injection of the solution into the formation without a significant increase in the injection pressure, which was confirmed by the low values of the resistance factor. The composition possesses selectivity of isolation effect, which is proved by more significant decrease of relative water permeability than relative oil permeability. The selectivity of the action provides a significant reduction in the water cut of the production well. Thus, DPG can serve as an effective tool to divert the filtration flows in the reservoir, blocking the highly permeable areas and channels in heterogeneous reservoirs.